Upregulation of genes related to bone formation by y-amino butyric acid and y-oryzanol in pre-germinated brown rice is via the activation of GABAB-receptors and reduction in serum IL-6 in rats - Muhammad Sani, Ismaila; Ismail, Maznah; Mahmud, Rozi; Abu Bakar @ Zakaria, Md Zuki; Imam, Mustapha Umar (Dove Medical Press, 2013)
Background: Osteoporosis and other bone degenerative diseases are among the most challenging non-communicable diseases to treat. Previous works relate bone loss due to osteoporosis with oxidative stress generated by free radicals and inflammatory cytokines. Alternative therapy to hormone replacement has been an area of interest to researchers for almost three decades due to hormone therapy-associated side effects. Methods: In this study, we investigated the effects of gamma-amino butyric acid (GABA), gamma-oryzanol (ORZ), acylated steryl glucosides (ASG), and phenolic extracts from germinated brown rice (GBR) on the expression of genes related to bone metabolism, such as bone morphogenic protein-2 (BMP-2), secreted protein acidic and rich in cysteine (SPARC), runt-related transcription factor 2 (RUNX-2), osteoblast-specific transcription factor osterix (Osx), periostin, osteoblast specific factor (Postn), collagen 1&2 (Col1&2), calcitonin receptor gene (CGRP); body weight measurement and also serum interleukin-6 (IL-6) and osteocalcin, in serum and bone. Rats were treated with GBR, ORZ, GABA, and ASG at (100 and 200 mg/kg); estrogen (0.2 mg/kg), or remifemin (10 and 20 mg/kg), compared to ovariectomized non-treated group as well as non-ovariectomized non-treated (sham) group. Enzyme-linked immunosorbent assay was used to measure the IL-6 and osteocalcin levels at week 2, 4, and 8, while the gene expression in the bone tissue was determined using the Genetic Analysis System (Beckman Coulter Inc., Brea, CA, USA). Results: The results indicate that groups treated with GABA (100 and 200 mg/kg) showed significant upregulation of SPARC, calcitonin receptor, and BMP-2 genes (P < 0.05), while the ORZ-treated group (100 and 200 mg/kg) revealed significant (P < 0.05) upregulation of Osx, Postn, RUNX-2, and Col1&2. Similarly, IL-6 concentration decreased, while osteocalcin levels increased significantly (P < 0.05) in the treated groups as compared to ovariectomized non-treated groups. Conclusion: GABA and ORZ from GBR stimulates osteoblastogenesis by upregulation of bone formation genes, possibly via the activation of GABAB receptors and by inhibiting the activity of inflammatory cytokines and reactive oxygen species. Therefore, it could be used effectively in the management of osteoporosis.